2016
DOI: 10.1521/pedi_2015_29_177
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Structurally About Narcissism: An Examination of the Five-Factor Narcissism Inventory and Its Components

Abstract: The Five-Factor Narcissism Inventory (FFNI) is a self-report measure of the traits linked to grandiose and vulnerable narcissism, as well as narcissistic personality disorder (NPD), from a five-factor model perspective (FFM). In the current studies, the factor structure of the FFNI was explored and the results supported the extraction of three factors: Antagonism (e.g., Arrogance), Neuroticism (e.g., Need for Admiration), and Agentic Extraversion (e.g., Authoritativeness). In Study 2, the FFNI factors manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
238
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(275 citation statements)
references
References 47 publications
21
238
3
3
Order By: Relevance
“…That is, beyond evidence from recent structural modeling work in humans indicating that “meanness operates as the ‘phenotypic glue’ that binds distinguishable facets of psychopathy together” (Drislane & Patrick, 2016), current study findings suggest that meanness may also be etiologically central to psychopathy, when considered as a broad trait dimension. This perspective is consistent in turn with the position of Miller and Lynam (2015), who argue that ‘antagonism’ is the central trait disposition underlying psychopathy as an omnibus condition, and with Patrick et al’s (2009) suggestion that meanness is the main source of overlap between subdimensions of psychopathy as it is commonly assessed in criminal offenders (cf.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…That is, beyond evidence from recent structural modeling work in humans indicating that “meanness operates as the ‘phenotypic glue’ that binds distinguishable facets of psychopathy together” (Drislane & Patrick, 2016), current study findings suggest that meanness may also be etiologically central to psychopathy, when considered as a broad trait dimension. This perspective is consistent in turn with the position of Miller and Lynam (2015), who argue that ‘antagonism’ is the central trait disposition underlying psychopathy as an omnibus condition, and with Patrick et al’s (2009) suggestion that meanness is the main source of overlap between subdimensions of psychopathy as it is commonly assessed in criminal offenders (cf.…”
Section: Discussioncontrasting
confidence: 49%
“…Paralleling relations among the YPI-Tri scales, the CHMP-Tri’s Boldness scale correlates to a moderate positive degree with both its Meanness and Disinhibition scales. As described previously (Latzman et al, 2016), the intercorrelations among triarchic dimension scales vary depending on the items used to index the constructs, with boldness and disinhibition scales correlating more when each contains items related to sensation-seeking, a trait that encompasses facets related to both of these triarchic constructs (Benning, Patrick, Blonigen, Hicks, & Iacono, 2005; Drislane & Patrick, 2016). This appears to be true of the CHMP-Tri Boldness and Disinhibition, which contain items indicative of daring approach and restless novelty-seeking, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…While this issue requires further scrutiny in future studies, our results argue against the WISC/WAIS subscales scores playing a major role in the PT performances. This result is consistent with previous research suggesting that impairments in social-cognitive processes, such as PT, cannot be entirely explained by IQ levels [17,55,75,76]. The investigation of the relationships between the IQ, executive functions and PT in antisocial individuals is beyond the aims of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Ackerman et al (2011) reported a three-factor structure: Leadership/Authority (11 items; e.g., "am assertive"), Grandiose Exhibitionism (10 items; e.g., "like to be the center of attention"), and Entitlement/ Exploitativeness (four items; e.g., "insist on getting respect"). We focus on this structure because (a) Ackerman et al (2011) found it to be robust and provided strong evidence of the validity of these dimensions across four large samples and (b) scales based on this structure have been widely used recently (e.g., Ackerman & Donnellan, 2013;Maxwell et al, 2011;Miller et al, 2014Miller et al, , 2015.…”
Section: Npi: Structure and Contentmentioning
confidence: 99%